Glucose Kinetics of Hyperglycemic Rainbow Trout: Effects of Exogenous Glucose and Exercise - Choi, Kevin (Université d'Ottawa / University of Ottawa, 2015)
This thesis investigates the ability of rainbow trout to modulate hepatic glucose production (Ra) and disposal (Rd). My goals were to determine: (1) if resting trout can modulate fluxes to cope with exogenous glucose; (2) how fluxes change during graded swimming; (3) how exogenous glucose affects swimming kinetics; and (4) if exogenous glucose affects cost of transport or performance. Results show that resting trout suppress Ra completely and stimulate Rd from 10.6 to 27.6 μmol kg-1 min-1. During swimming, fluxes increase from 15.6 to 21.9 μmol kg-1 min-1, but only at speeds >2.4 BL s-1. When given glucose, trout suppress Ra from 16.4 to 4.1 μmol kg-1 min-1 and stimulate Rd from 16.4 to 40.1 μmol kg-1 min-1. Glucose lowers metabolic rate but does not affect critical swimming speed. Therefore, this research shows that rainbow trout have a much better capacity for glucoregulation than generally suggested by current literature.
Keywords: Hepatic glucose production; Glucoregulation; Exogenous glucose; Carbohydrate metabolism; Swimming; Continuous tracer